ELECTRONIC JURISDICTION, METAVERSE, ARTIFICIAL INTELLIGENCE, DIGITAL PERSONALITY, DIGITAL AVATAR, NEURAL NETWORKS: THEORY, PRACTICE, PERSPECTIVE (World Science, 2022)
Scientific and technological revolution 4.0 (The Fourth Industrial Revolution) has created a huge window of opportunity for a variety of creative technologies. At the same time it launched the emergence and development of modern social relations in the electronic space - the metaverse. In fact, today all the prerequisites for the scientific and technological revolution 5.0 and social revolution 5.0, which radically changes the role of human in the social structure, while changing the social structure, creating new social groups, social institutions, electronic ecosystems and metaverse. Modern social relations in the electronic space are multi-vector and can be divided according to the variety of objects, subjects and characteristics of the relationship between them, namely: the subjective and object basis of identification of social relations. Thus, the subjective basis for the identification of social relations is the social communities of people, and the object one is information and communication technologies and its products. Legal science is a social science, as it performs gnoseological and heuristic functions that determine the direction of scientific research and scientific predictions, studying the relations between people, groups of people, people and state institutions. The results of research are practical improvement of legislation on a scientific basis, development of draft normative legal acts, scientific examinations, etc.However, the current practice indicates that modern laws are created very slowly, without necessary and sufficient detaliztion of terms and basic concepts.It is difficult to overestimate the correctness, accuracy and consistency with the current legislation of definitions of legal terms. Unfortunately, the current legislation is unable to regulate public relations, which are rapidly evolving in the electronic space using digital technologies, artificial intelligence, Internet of Things (IoT), digital identity, digital avatars and other technologies, especially those that may restrict human rights and freedom. In fact, along with the creation of new social relations in the metaverse, it is necessary to create an electronic jurisdiction - the scope of application of opportunities by the subject of competence or the sphere to which the right applies.The author’s definitions "metaverse (cyberspace)", "electronic avatar", "electronic personality", "electronic jurisdiction", "cybercrime", "kidnapping of electronic avatar or electronic personality", "artificial intelligence" and "neural networks" are proposed in the article.Six postulates of the main directions of development of social relations with the use of technologies of the metaverse, artificial intelligence, artificial neural networks, robotic systems, medical and military lost products and devices are formed.Proposals for the creation of a comprehensive electronic jurisdiction, conceptual and categorical apparatus, definition of subjects and objects, rights, duties and responsibilities in the metaverse and in the use of artificial intelligence technologies, artificial neural networks, robots, etc. are provided.